Analysis of knockout mutants reveals non-redundant functions of poly(ADP-ribose)polymerase isoforms in Arabidopsis - Pham, Phuong Anh (2015)
The enzyme poly(ADP-ribose)polymerase (PARP) has a dual function being involved both in the poly(ADP-ribosyl)ation and being a constituent of the NAD+ salvage pathway. To date most studies, both in plant and non-plant systems, have focused on the signaling role of PARP in poly(ADP-ribosyl)ation rather than any role that can be ascribed to its metabolic function. In order to address this question we here used a combination of expression, transcript and protein localization studies of all three PARP isoforms of Arabidopsis alongside physiological analysis of the corresponding mutants. Our analyses indicated that whilst all isoforms of PARP were localized to the nucleus they are also present in non-nuclear locations with parp1 and parp3 also localised in the cytosol, and parp2 also present in the mitochondria. We next isolated and characterized insertional knockout mutants of all three isoforms confirming a complete knockout in the full length transcript levels of the target genes as well as a reduced total leaf NAD hydrolase activity in the two isoforms (PARP1, PARP2) that are highly expressed in leaves. Physiological evaluation of the mutant lines revealed that they displayed distinctive metabolic and root growth characteristics albeit unaltered leaf morphology under optimal growth conditions. We therefore conclude that the PARP isoforms play non-redundant non-nuclear metabolic roles and that their function is highly important in rapidly growing tissues such as the shoot apical meristem, roots and seeds.